Association between mean platelet volume and disease severity in patients with psoriasis and psoriatic arthritis - Kılıç, Sevilay; Reşorlu, Hatice; Işık, Selda; Oymak, Sibel; Akbal, Ayla; Hiz, Meliha Merve; Öğretmen, Zerrin (Advances in Dermatology and Allergology/Postępy Dermatologii i Alergologii, 2017)
Introduction: Mean platelet volume (MPV) is an important marker that shows the activation and function of the platelets, which is effective in the inflammatory diseases. Aim : To show the relationship between MPV and the development of psoriatic arthritis (PA) in patients with psoriasis vulgaris (PV) and the correlation between MPV and psoriasis severity score (PASI). Material and methods : Our study included 116 patients with psoriatic arthritis (68 female, 48 male) and 41 patients in the psoriasis group (19 female, 22 male) and 90 subjects in the control group (55 female, 35 male). The demographic data of the patients, duration of disease, PASI, the nature of the disease were evaluated retrospectively. Results : Mean platelet volume levels of both the PV group (8.79 ±0.86 fl) and the PA group (9.18 ±1.26 fl) were significantly higher compared to the control group (8.42 ±0.74 fl). There was a weak statistically positive correlation between the PASI and the MPV according to the correlation analysis (r = 0.165; p = 0.046). Conclusions : Our results show that MPV may be helpful as an indicator of the clinical course of PV and PA. In this regard, that study should be supported by prospective studies to find strong correlations.